ANALISIS CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA APLIKASI MAKANAN ONLINE - Nika Sintesa; Enny Diah Astuti; Widiarti Lestariningsih (POLITEKNIK LP3I JAKARTA, 2022)
Digital business is developing very fast, especially in the food sector. Customers do not have to come to the restaurant to get the food they want. Customers can order it through a digital app anytime, anywhere. The purpose of this study was to find out the analysis of brand image and service quality on customer satisfaction in online food applications (Go Food, Grab Food, Shopee Food). The study used a quantitative approach. The research results of brand image and service quality analysis have a significant impact on customer satisfaction, and some brand image and service quality affect customer satisfaction variables. We recommend the management to maintain the excellent service provided and even develop the advantages of using online food applications in order to achieve customer satisfaction.Keywords: Brand Image, Service Quality, Customer Satisfaction